Southern elephant seals north of the Antarctic Polar Front - Lewis, Mirtha Noemi; Campagna, Claudio; Marin, Maria Rosa; Fernandez, Teresita Josefa (Antarctic Science)
This paper reports on sightings and dispersion of individual southern elephant seals (Mirounga leonina) along the Atlantic and Pacific coasts of South America based on reports of tagged/marked seals from Patagonia and of animals of unknown origin. From 154 sightings, encompassing at least 354 individuals, we found that individuals dispersed to subequatorial latitudes on both sides of the continent, and to more temperate sites, in the Magellanic region of Tierra del Fuego. Nineteen sites were visited by tagged seals from the established colony of Península Valdés (PV, Argentina). PV and the smaller seal population of the Falklands/Malvinas were regularly connected by adults of both sexes. There were more sightings of males than females. No incipient new breeding colonies were found along the Atlantic coast of South America. Some observations coincided with places where elephant seals had been recorded or exploited in the seventeenth and eighteenth centuries. A shortage of suitable habitat for expansion and proximity to predictable food could act as a stabilizing process preventing colonization of new areas from PV. Dispersion data, coherent with population genetics, support a Patagonian elephant seal stock. Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Campagna, Claudio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos Fil: Marin, Maria Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Fernandez, Teresita Josefa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina